Comportamento de oxidação em temperaturas elevadas de ligas NiTiNb com efeito memória de forma - Martins Júnior, Claudio Beserra (2021)
Shape memory alloys (SMA) of the Nickel-Titanium (NiTi) system are currently the most commercially important, due to their excellent mechanical properties, high shape recovery and biocompatibility. Such a unique set of properties has led this class of materials to find a wide range of applications in various industrial sectors. However, obtaining these alloys at a low production cost is still a major challenge for the industry, largely due to oxidation during the processing, which can negatively affect the shape memory effect (SME). Thus, investigations to improve the oxidation resistance of these alloys deserve attention. Despite being little explored, the Nb addition, up to 7 at.%, has proven to be very effective in reducing oxidation rates. Research with higher contents has not been found in the literature. Therefore, the aim of this work was to evaluate the influence of Nb addition at contents between 9 at.% and 12 at.% on the high temperature oxidation behavior of NiTi SMA, by means of thermogravimetric analyses for up to 100 h at temperatures of 800 °C, 900 °C, and 1,000 °C. It was found that at all the studied temperatures, the alloys followed the parabolic oxidation rate law, and the Nb addition reduced the rate constants (kp) by at least 8 times. The formed oxide layer was analyzed by X-ray diffraction (XRD) and scanning electron microscopy with energy dispersive X-ray spectroscopy analysis system (SEM/EDS). The improvement in oxidation resistance was explained in terms of Nb rich regions forming in the oxidation product layer, where the replacement of Ti4+ by Nb5+ reduces the number of defects that influence oxidation rates. It was also seen that the addition of Nb improves the adhesion of the layer.